two variables

----------
(7.10)
$a^2-b^2=(a-b)(a+b)$
----------
(7.17.1)
$a^3-b^3=(a^2+ab+b^2)(a-b)$
----------
(7.19)
$a^4-b^4=(a^2+b^2)(a+b)(a-b)$
----------
(7.17.2)
$a^3+b^3=(a^2-ab+b^2)(a+b)
----------
$(a+b)^3-a^3-b^3=3ab(a+b)$
----------
$(a+b)^5-a^5-b^5=5ab(a+b)(a^2+ab+b^2)$
----------
$(a+b)^7-a^7-b^7=7ab(a+b)(a^2+ab+b^2)^2$
----------
$(a+b)^{11}-a^{11}-b^{11}=11ab(a+b)(a^2+ab+b^2)((ab)^2(a+b)^2+(a^2+ab+b^2)^3)$
----------
$(a+b)^{13}-a^{13}-b^{13}=13ab(a+b)(a^2+ab+b^2)^2(2(ab)^2(a+b)^2+(a^2+ab+b^2)^3)$
----------
$(a^4-2ab^3)^3 + (a^3b+b^4)^3 = (b^4-2a^3b)^3 + (ab^3+a^4)^3$~~~~~~~~~~(Vieta)
----------
$(3a^2+5ab-5b^2)^3 + (4a^2-4ab+6b^2)^3 + (5a^2-5ab-3b^2)^3 = (6a^2-4ab+4b^2)^3$~~~~~~~~~~(Ramanujan)
----------
$(a^2+9ab-b^2)^3+(12a^2-4ab+2b^2)^3=(9a^2-7ab-b^2)^3+(10a^2+2b^2)^3$~~~~~~~~~~(Ramanujan)
----------
$(a^4-4b^4)^4 + 2(2a^3b)^4 + 2(4ab^3)^4 = (a^4+4b^4)^4$
----------
(7.35)
$a^n-b^n=(\sum_{k=1}^{n}a^{k-1}b^{n-k})(a-b)$
----------
(47.13)
$\begin{vmatrix}
a&b&b\\ 
b&a&b\\ 
b&b&a
\end{vmatrix}
=(a+2b)(a-b)^2
----------
(47.62)
\begin{bmatrix}
a&b&b&b\\
b&a&b&b\\ 
b&b&a&b\\ 
b&b&b&a 
\end{bmatrix}
=(a+3b)(a-b)^3
----------